Crisis Volunteerism is the New Black?—Exploring the Diversity of Voluntary Engagement in Crisis Management. Issue 3 (19th March 2019) - Strandh, Veronica
Abstract : Both crisis research and crisis management policy suggest that crisis management experiences a "participatory turn" and it seems to be a renewed interest in the topic of crisis volunteerism. However, the voice of volunteer organizations, paradoxically, appears to be missing in research. This article builds on an interview study (26 interviews) with different types of voluntary organizations in Sweden. It explores two aspects of crisis volunteerism (i) the diversity of crisis volunteerism and (ii) the changing landscape of crisis volunteerism. The Disaster Research Center (DRC) typology is used to understand different types of volunteering and how different organizational types relate to each other. The empirical material shows that a significant amount of voluntary engagement with relevance to crisis management takes place outside the realm of core crisis management actors. An important finding is that the number of avenues where voluntary engagement is needed has expanded, and as a result, we need to engage new volunteer groups in society. Hence, the study suggests a more adaptive and inclusive understanding of the phenomenon of crisis volunteerism. Abstract : 摘要: 危机研究和危机管理政策都认为危机管理正在经历一次"参与转变"，并且这种转变似乎重新引起了对危机志愿服务（crisis volunteerism）话题的关注。然而与之相悖的是，目前似乎还没有关于志愿机构的研究。本文分析了一项针对瑞典地区不同类型志愿机构的采访研究（共26次）。本文探索了危机志愿服务的两大方面：i)危机志愿服务的多样性ii)危机志愿服务不断变化的景象。本文使用灾害研究中心(DRC)提出的类型学，以理解不同形式的志愿服务，以及不同组织类型如何相互关联。实证材料显示，与危机管理有关的相当一部分志愿参与发生在核心危机管理行动者所涉范围之外。一项重要发现表明，需要志愿参与的地点数量已经扩大，因此需让新的志愿群体参与其中。本文就此建议，对危机志愿服务现象的理解应更具适应性和包容性。 Abstract : Resumen: Tanto la investigación de las crisis como de las políticas de gestión de crisis sugiere que la gestión de crisis está pasando por un "turno participativo" y parece haber un renovado interés por el tema del voluntariado en las crisis. Sin embargo, la voz de las organizaciones de voluntarios, paradójicamente, parece estar ausente en la investigación. Este artículo se basa en un estudio de entrevistas (26 entrevistas) con diferentes tipos de organizaciones voluntarias en Suecia. Explora dos aspectos del voluntariado en las crisis i) la diversidad del voluntariado en las crisis ii) el panorama cambiante del voluntariado en las crisis. La tipología del Centro de Investigación de Desastres (DRC) se usa para comprender diferentes tipos de voluntariado y cómo diferentes tipos de organizaciones se relacionan entre sí. El material empírico muestra que una cantidad significativa de participación voluntaria con relevancia para la gestión de crisis tiene lugar fuera del ámbito de los actores centrales de la gestión de crisis. Un hallazgo importante es que el número de situaciones donde se necesita la participación de voluntarios ha crecido, y como resultado, necesitamos que nuevos grupos voluntarios participen en la sociedad. Por ende, el estudio sugiere un entendimiento más adaptativo e inclusivo del fenómeno del voluntariado en las crisis.